Unravelling the evolutionary complexity of RNA viruses - Tully, Damien (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2009)
Viruses are a delicate group of organisms renowned for the serious diseases they inflict. They affect all cellular life and are subdivided into RNA-based and DNA-based viruses depending on the type of genomic nucleotide material they contain. Those that are RNA-based appear to contain more emergibility owing to their rapid rates of evolutionary change and are responsible for diseases such as Human Immunodeficiency Virus (HIV), Hepatitis C Virus (HCV) and Foot and- Mouth Disease Virus (FMDV). The importance of dissecting the evolutionary complexity associated with such organisms is twofold: to improve our overall understanding of the mechanisms driving pathogenic viruses and to aid in predicting what genomic regions/structure motifs may be important for future antiviral therapeutics.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin.